2008
DOI: 10.1158/0008-5472.can-08-1522
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mammalian Target of Rapamycin (mTOR)–Targeted Cancer Therapy by Preventing mTOR/Raptor Inhibition-Initiated, mTOR/Rictor-Independent Akt Activation

Abstract: It has been shown that mammalian target of rapamycin (mTOR) inhibitors activate Akt while inhibiting mTOR signaling. However, the underlying mechanisms and the effect of the Akt activation on mTOR-targeted cancer therapy are unclear. The present work focused on addressing the role of mTOR/rictor in mTOR inhibitor-induced Akt activation and the effect of sustained Akt activation on mTOR-targeted cancer therapy. Thus, we have shown that mTOR inhibitors increase Akt phosphorylation through a mechanism independent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
168
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 28 publications
23
168
1
2
Order By: Relevance
“…In addition, mTORC1 knockdown with raptor siRNA did not block rapamycin-induced Akt phosphorylation in DLBCL cells. This finding is in contrast with the studies in lung cancer cells where rapamycin increased Akt phosphorylation independent of mTORC2 32 and consistent with the results of others in different For personal use only. on May 10, 2018. by guest www.bloodjournal.org From model systems.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, mTORC1 knockdown with raptor siRNA did not block rapamycin-induced Akt phosphorylation in DLBCL cells. This finding is in contrast with the studies in lung cancer cells where rapamycin increased Akt phosphorylation independent of mTORC2 32 and consistent with the results of others in different For personal use only. on May 10, 2018. by guest www.bloodjournal.org From model systems.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, transient disruption of the mTORC1 complex in human lung cancer cells resulted in increased phosphorylation of Akt S473 without a detectable effect on S6K1 phosphorylation confirming that these 2 events are not always concurrent. 49 Our results clearly indicate a role for Mer in mTOR-mediated feedback inhibition of Akt. Mer may also play a role in regulation of mTOR activity.…”
Section: Discussionmentioning
confidence: 54%
“…In some other studies using EBV-positive B cell lines (21) or other cell lines (36,37), inhibition of 4E-BP1 phosphorylation by rapamycin was partial, whereas inhibition of p70S6K phosphorylation was complete. The reason is uncertain, but activation of survival signaling pathways such as Akt may prevent complete inhibition of 4E-BP1 phosphorylation (37). It has been shown that rapamycin induces Akt activation through an mTOR complex, resulting in the attenuating growth-inhibitory effect of rapamycin (37).…”
Section: Discussionmentioning
confidence: 90%